2022
DOI: 10.1098/rsos.210784
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol-loaded chitosan–pectin core–shell nanoparticles as novel drug delivery vehicle for sustained release and improved antioxidant activities

Abstract: Resveratrol, chemically known as 3,5,4'-trihydroxy-trans-stilbene, is a natural polyphenol with promising multi-targeted health benefits. The optimal therapeutic uses of resveratrol are limited due to its poor solubility, rapid metabolism and low bioavailability. To address the issues, we have encapsulated resveratrol inside the nanosized core made of chitosan and coated this core with pectin-shell in order to fabricate a drug delivery vehicle which can entrap resveratrol for a longer period of time. The core–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…FE-TEM/SAED images were obtained to obtain information on the internal morphology and particle distribution, where FE-TEM analysis revealed the formation of monodisperse core-shell particles with a spherical core of about 13 nm and a shell with an average thickness of about 4 nm; finally, SAED imaging showed circles and bright spots that highlighted the crystalline behavior of the encapsulated RSV. HR-TEM analysis confirmed the crystalline nature and, in relation to the amount of used pectin, showed an increase in the thickness of the coating [81].…”
Section: Morphology and Size Of Carriersmentioning
confidence: 59%
“…FE-TEM/SAED images were obtained to obtain information on the internal morphology and particle distribution, where FE-TEM analysis revealed the formation of monodisperse core-shell particles with a spherical core of about 13 nm and a shell with an average thickness of about 4 nm; finally, SAED imaging showed circles and bright spots that highlighted the crystalline behavior of the encapsulated RSV. HR-TEM analysis confirmed the crystalline nature and, in relation to the amount of used pectin, showed an increase in the thickness of the coating [81].…”
Section: Morphology and Size Of Carriersmentioning
confidence: 59%
“…Several studies have shown that biopolymer nanoparticle-mediated delivery can be a useful approach for improving the bioavailability of RSV. For example, Sarma et al encapsulated RSV in chitosan–pectin core-shell NPs, which resulted in enhanced RSV bioavailability (almost 30 h) and better in vitro radical scavenging activity than that of free RSV [ 166 ]. Sanna et al developed chitosan-alginate-coated poly(D,L-lactide-co-glycolide) nanoparticles loaded with RSV that provided significant protection against light-induced degradation [ 167 ].…”
Section: Rsv Modificationsmentioning
confidence: 99%
“…In addition, it showed enhanced in vivo absorption, prolonged duration of action, and increased relative bioavailability by 3.5-fold when compared to free drugs. Sarma and coworkers developed chitosan-pectin core-shell nanoparticles loaded with resveratrol to improve its antioxidant activity and obtain prolonged release [176]. Liu and coworkers developed α-lactalbumin and chitosan core-shell nanoparticles loaded with resveratrol [177].…”
Section: Resveratrolmentioning
confidence: 99%